The Influence of Intellectual Intelligence and Spiritual Intelligence on Employee Performance at Bank Syariah Indonesia KCP Cirebon Sisingamangaraja: - Nidia Wulan Sari (Universitas Dehasen Bengkulu, 2026)
This study aims to analyze the influence of intellectual intelligence and spiritual intelligence on employee performance at Bank Syariah Indonesia (BSI) KCP Cirebon Sisingamangaraja. This research uses a quantitative approach with an explanatory design, and data were collected using a Likert scale questionnaire (1–5). The study sample consisted of BSI KCP Cirebon Sisingamangaraja employees selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Squares (PLS) to examine the relationships between variables. The results indicate that intellectual intelligence has a positive and significant effect on employee performance, with an Original Sample (O) value of 0.632, T-statistics of 16.579, and P-value of 0.000. Additionally, spiritual intelligence also has a positive and significant effect on employee performance, with an Original Sample (O) value of 0.440, T-statistics of 10.734, and P-value of 0.000. These findings suggest that enhancing employees’ intellectual and spiritual intelligence can effectively improve their performance. Based on the results, it is recommended that BSI management implement programs to develop employees’ intellectual and spiritual intelligence to support better work quality, motivation, and work ethic.